Comparative assessment of support plates' influences on delamination damage in micro-drilling of CFRP laminates - KENTLİ, AYKUT (ELSEVIER SCI LTD, 2017)
In this study, drilling induced delamination damage which occurs during micro-drilling of CFRP laminates was investigated experimentally under variable cutting speeds and feed rates. Unlike the previous studies, the delamination factors in micro-drilling of CFRP laminates were precisely calculated and compared for supported and unsupported cases. Using support plates which are placed front and rear sides of the CFRP laminate is one of the methods which limits the delamination damage. Two different setups of support plates were used in the experiments. In the first setup, the entry board was aluminum plate and the backing board was phenolic plate. In the second setup, the entry board was brass plate and the backing board was wooden plate. Hole pictures were taken from each CFRP laminate by using a digital microscope. The first, the middle and the last three holes were inspected from the front and rear sides of the CFRP laminate. Minitab was used to evaluate the experiments' outputs, and response surface method was used to optimize the process parameters. It has been revealed that the delamination damage in micro-drilling differs from the delamination damage in conventional drilling of CFRP laminates. Obviously, the process exhibits unusual delamination behavior as process size decreases. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Micro-drilling; CFRP laminate; Delamination damage; Support plates; COMPOSITE-MATERIALS; CHIP FORMATION; SIZE; HOLE